The Role of Consent in Rape Legislation: A Critical Legal Analysis of Judicial Interpretation and Societal Impact - Manu Sharma (Journal of Informatics Education and Research, 2025)
Consent is the foundation of rape legislation, although its legal interpretation is contentious and laden with patriarchal prejudices. This paper critically analyzes the development of the notion of consent in Indian rape law, emphasizing statutory amendments, judicial interpretations, and societal discourse. Utilizing doctrinal legal research, feminist jurisprudence, and comparative analyses from jurisdictions such the United Kingdom and Germany, the study examines how Indian courts have managed the conflicts between strict textual legislative compliance and survivor-focused methodologies. The findings indicate that, despite the post-2013 amendments incorporating affirmative wording highlighting "unequivocal voluntary agreement," substantial deficiencies persist, particularly the marital rape exception and the inconsistent judicial handling of consent acquired through fraudulent promises. Comparative findings indicate that international human rights treaties and foreign jurisdictions are progressively endorsing affirmative consent as the global standard, including addressing novel types of sexual assault, like stealthing and upskirting. This article contends that India's rape legislation must transition unequivocally towards a comprehensive affirmative consent framework that emphasizes autonomy, dignity, and equality. This kind of change is necessary to bring domestic law in line with constitutional norms and international human rights commitments, ensuring justice and bodily integrity for survivors.